2015
DOI: 10.1158/1538-7445.sabcs14-s3-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-04: The phase III ICE study: Adjuvant Ibandronate with or without capecitabine in elderly patients with moderate or high risk early breast cancer

Abstract: Background: Although approximately 50% of newly diagnosed breast cancers arise in women above 65 years old they are underrepresented in clinical trials. The ICE study was designed to investigate if a mono-chemotherapy with capecitabine in addition to the third generation bisphosphonate ibandronate will improve the outcome compared to ibandronate alone in elderly breast cancer patients with medium and high risk primary breast cancer not suitable for standard chemotherapy. Methods: This is a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
14
0
3
Order By: Relevance
“…In elderly patients, the CALGB 49907 trial compared standard adjuvant therapy with either cyclophosphamide/methotrexate/fluorouracil (CMF) or AC versus capecitabine monotherapy and found that capecitabine had inferior efficacy with regard to both 3‐year RFS and OS . Similarly in the ICE trial, also in a population of elderly patients with breast cancer, no advantage in either 5‐year DFS or OS was observed with the addition of capecitabine to adjuvant therapy with ibandronate alone .…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, the CALGB 49907 trial compared standard adjuvant therapy with either cyclophosphamide/methotrexate/fluorouracil (CMF) or AC versus capecitabine monotherapy and found that capecitabine had inferior efficacy with regard to both 3‐year RFS and OS . Similarly in the ICE trial, also in a population of elderly patients with breast cancer, no advantage in either 5‐year DFS or OS was observed with the addition of capecitabine to adjuvant therapy with ibandronate alone .…”
Section: Discussionmentioning
confidence: 99%
“…Отмечено, что трастузумаб может вызвать сердечную недостаточность [25]. Комбинация режимов трастузумаба с доцетакселом и карбоплатином сходна по эффективности с трастузумабом и антрациклинсодержащей ХТ, но ассоциируется с меньшей сердечной токсичностью [26][27][28]. Однако также имеются данные о кардиотоксичности антрациклинов, в то время как безантрациклиновые схемы могут быть использованы без серьезного риска осложнений сердечно-сосудистый системы у пожилых.…”
Section: химиотерапияunclassified
“…В другом исследовании (Ibandronate and Capecitabine in Elderly Women -ICE) 1358 больных РМЖ в возрасте 65 лет и старше были рандомизированы для получения ибандроната в течение 2 лет и получения ибандроната (2 года) плюс капецитабин в течение 6 курсов. Анализ исследования продемонстрировал сходные результаты между группами лечения через 3 года, а также не выявил никакой разницы в ОВ [28]. Более того, как в исследованиях CALGB 49907, так и в исследовании ICE у пациентов, получавших капецитабин, чаще отмечался токсический эффект, а переносимость была меньше ожидаемой.…”
Section: обзоры литературыunclassified
“…Results showed no difference between the two treatment arms for the primary endpoint of three-year invasive DFS: 85.4% in women treated with capecitabine plus ibandronate vs. 84.3% in the ibandronate-alone arm; the five-year invasive DFS was 78.8% vs. 75%, respectively. Similarly, there was no difference in OS at the end of three years (95% vs. 94%) and five years (90% vs. 88%) [ 31 ]. The negative results of ICE study did not favor the use of capecitabine monotherapy, thus complementing the results of CALGB 49907 in supporting the use of combination chemotherapy as a standard adjuvant treatment for elderly women over that of capecitabine alone.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%